Development of Spatial Weighted Matrix based on Transportation Connectivity for Archipelago Provinces in Indonesia - Sedubun, Debora Ribka; Yudistira, Yudistira; Laamena, Novita Serly; Salhuteru, Rosalina (Jurusan Matematika FMIPA Universitas Pattimura, 2023)
The application of spatial statistics is now commonly used in analysis of phenomena of strategic indicators in Indonesia, including in archipelago provinces. However, application of spatial statistics in archipelago provinces is constrained by spatial weighted matrix that are less relevant in identifying the spatial effects of indicators, due to enormous number of territories which not directly bordered by land. Meanwhile, transportation connectivity in archipelago provinces has expanded far beyond its administrative boundaries. Through this research, we tried to formulate concept in development of spatial weighted matrix based on transportation connectivity between regency/city in archipelago provinces. Our research used primary data processing methods as well as literature studies, with used the data of sea and air transport routes between regencies and cities in the 3 archipelago provinces: Maluku, Maluku Utara, and Kepulauan Riau. We developed several types of spatial weighted matrix based on transportation connectivity between regency/city in those three provinces, as well concepts in combining such matrix with other kinds of spatial weighted matrix. With our research, it is hoped that could trigger more spatial research related to strategic indicators in archipelago provinces in Indonesia.